Answer: If two angles of one triangle are congruent to two angles of another triangle, then the third pair of angles is also congruent
Step-by-step explanation:
The <em>third angle theorem</em> says that if two angles in one triangle are congruent to two angles in another triangle, then the third pair of angles must also congruent. This is called the Third Angle Theorem.
Let ΔABC and ΔPQR are two triangles such that
∠A≅∠P and ∠B=∠Q.......(1)
Also ∠R=180°-(∠P+∠Q) [By angles sum property in ΔPQR ]......(2)
∠C=180°-(∠A+∠B) [By angles sum property in ΔABC]
⇒∠C=180°-(∠P+∠Q) [from (1)]
⇒∠C=∠R [from (2)]
Hence proved.